2022
DOI: 10.3389/fpls.2022.766493
|View full text |Cite
|
Sign up to set email alerts
|

Rotten Hazelnuts Prediction via Simulation Modeling—A Case Study on the Turkish Hazelnut Sector

Abstract: The quality defects of hazelnut fruits comprise changes in morphology and taste, and their intensity mainly depends on seasonal environmental conditions. The strongest off-flavor of hazelnuts is known as rotten defect, whose candidate causal agents are a complex of fungal pathogens, with Diaporthe as the dominant genus. Timely indications on the expected incidence of rotten defect would be essential for buyers to identify areas where hazelnut quality will be superior, other than being useful for farmers to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…In terms of the crop susceptibility windows, we established the DEFHAZ model to have possible infection until the end of May, which we based on the regression analysis using a stepwise approach, and which is in partial agreement with Valeriano et al [22], who considered hazelnut to be most susceptible to infections during female flowering, and therefore over a narrower period. To confirm the reasonable period for primary infection, we require studies with the artificial inoculation of D. eres α conidia in planta, and possibly with the subsequent incubation at different temperatures.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…In terms of the crop susceptibility windows, we established the DEFHAZ model to have possible infection until the end of May, which we based on the regression analysis using a stepwise approach, and which is in partial agreement with Valeriano et al [22], who considered hazelnut to be most susceptible to infections during female flowering, and therefore over a narrower period. To confirm the reasonable period for primary infection, we require studies with the artificial inoculation of D. eres α conidia in planta, and possibly with the subsequent incubation at different temperatures.…”
Section: Discussionsupporting
confidence: 54%
“…In a more recent paper, the authors present a model to predict rotten hazelnut kernels; in this case, they did not focus on a specific causal agent but included the Diaporthe spp. [22]. The authors confirmed the strict dependence of rotten hazelnuts on the precipitation amount and timing, and on the role of the plant susceptibility, and they suggest the effects of other environmental and agronomic factors on the rot incidence that they did not include in the model.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…However, in this case, as our studies have shown, it is desirable to leverage different characteristics of varieties for the development and generation of yields, which allows for a more flexible strategy (Kizilkaya et al, 2022;Valeriano et al, 2022). The generation of yield depends on many parameters of both the plant itself and its fruit, which has been repeatedly noted above.…”
Section: Discussionmentioning
confidence: 65%